Effect of Occupational Health Safety, Work Discipline, Motivation, and Work Environment on Employee Performance - Djanuar, Tasya Meyrizka; Krisnandi, Herry; Digdowiseiso, Kumba (Ridwan Institute, 2024)
This study aims to determine and analyze the effect of occupational health and safety, work discipline, motivation, and work environment on the performance of PT employees. Pangansari Utama. This type of research uses descriptive quantitative methods, inferential analysis using primary data in a questionnaire to 100 respondents, and data analysis using multiple linear analysis. The following regression equation is obtained from the data that met the validity, reliability, classical assumption, and model tests: Y = 5.369 + 0.280 X1 + 0.229 X2 + 0.186 X3 + 0.219 X4. The results showed that occupational health and safety, work discipline, motivation, and work environment positively and significantly affected employee performance. A significant variable is occupational health and safety (X1), with a significant level of 0.001. To improve employee performance, PT. Pangansari Utama needs to pay attention and know the problem because it can be used to correct weaknesses and maintain the effectiveness of occupational health and safety, work discipline, motivation and work environment properly and maximally.